Factors influencing international and U.S. dentists' interest in advanced periodontal education: a pilot study - Andre Paes B. da Silva; Hazem Saqqal; Andrew Guirguis; Uma M. Irfan (BMC, 2021)
Abstract Background The enrollment of international periodontal students in U.S. dental schools has been increasing in recent years. Interest in applying to a periodontics specialty program may differ between U.S and international dental school graduates. The purpose of this study is to assess, from the perspective of periodontal residents, (1) factors that interest dental students to apply to periodontics programs and (2) differences in background and interest between U.S and international graduates. Methods A 20-question survey was sent out electronically to periodontics residents. The survey questions were designed to obtain information on the participants' backgrounds, factors that influenced them to specialize in periodontics, and their preferred features of graduate periodontics programs. The data were analyzed using descriptive statistics for socio-demographic variables, a Wilcoxon two sample test to compare mean Likert scale scores, and Fisher's exact test for associations between comparison groups. Results Of the two hundred residents invited to participate, 28% responded. The majority of the respondents stated that interest in implantology, previous exposure to periodontal procedures, interest in improving periodontal surgery skills, a good relationship with periodontics faculty, the residency curriculum, advanced program and faculty reputation as influencing factors in selecting periodontics as specialization. The majority of international graduates have up to $50,000 dollars in student debt; by comparison, half of the domestic graduates have a debt of over $250,000 dollars (p ≤ 0.05). Working experience as a dentist was significantly greater among international residents (73%) in comparison to U.S graduates (32%). In contrast with international graduates, U.S graduates more frequent reported that good relationships with the periodontics predoctoral faculty contributed to their interest in periodontics (p ≤ 0.05). Program cost and location had a greater impact on the decision of U.S. graduates than international graduates (p ≤ 0.05). Conclusions Overall, factors associated with personal finance and predoctoral education have a greater impact on the decision of American graduates than international graduates to pursue an advanced education in periodontics, which may influence the increased enrollment of international students.